Proportioning design method for nano-filler modified fast electromagnetic response type asphalt mixture

By designing the ratio of nanofillers and asphalt and pushing the asphalt mixture backwards, the problem of difficulty in achieving rapid electromagnetic response and good comprehensive performance in the existing technology is solved, and the rapid electromagnetic response and comprehensive performance of asphalt mixture are improved.

CN119920372APending Publication Date: 2025-05-02CHINA RAILWAY NO 2 ENG GROUP CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411862017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-17
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing asphalt mixture grading design method is difficult to achieve a good balance between fast electromagnetic response characteristics and comprehensive performance, and cannot meet the requirements of modern road projects for the heating efficiency and comprehensive performance of asphalt mixture.

Method used

By designing the ratio of nanofillers and asphalt, the electromagnetic response effect of the material is initially determined, and the asphalt mixture grading is reversely pushed back by determining the nano-glue ratio and oil-stone ratio, the ratio design of the fast electromagnetic-responsive asphalt mixture is achieved.

Benefits of technology

The rapid electromagnetic response characteristics and comprehensive performance of asphalt mixture are improved, the complexity of the traditional design process is reduced, and the optimal amount of modified materials is accurately obtained, meeting the needs of modern road engineering.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920372A_ABST
    Figure CN119920372A_ABST
Patent Text Reader

Abstract

The invention relates to a proportion design method for a nano-filler modified fast electromagnetic response type asphalt mixture. The proportion design method comprises the following steps: S1, designing the proportion of nano-filler and asphalt; s2, verifying the mechanical properties of the asphalt; s3, designing the gradation of the asphalt mixture; and S4, verifying the performance of the asphalt mixture. The method can accurately determine the parameters of the mixture, verify the performance and construct and deduce an electromagnetic parameter formula, and has the effects of improving the road construction efficiency, ensuring the quality, promoting technical innovation, saving energy, protecting the environment and being wide in adaptability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of road engineering materials and relates to a method for designing the proportion of a nano-filler modified fast electromagnetic response asphalt mixture. Background Art

[0002] In the field of road engineering, the traditional asphalt mixture gradation design method has certain limitations. With the continuous development of science and technology and the improvement of road performance requirements, the existing gradation design method is difficult to meet actual needs in some aspects. On the one hand, traditional gradation design often cannot achieve fast electromagnetic response characteristics. In modern transportation, for some special sections or areas with specific needs, asphalt mixtures need to be able to respond quickly to electromagnetic heating to achieve functions such as rapid deicing and snow melting, and improve road safety and traffic efficiency.

[0003] However, most of the existing gradation design ideas are sequential logic, which first assumes the modifier dosage and then determines the specific oil-stone ratio and gradation. This method is difficult to effectively find the optimal dosage point for improving the heating efficiency of asphalt mixtures, and cannot meet the requirements of fast electromagnetic response. On the other hand, the comprehensive performance of traditional gradation design needs to be improved. In terms of mechanical properties, such as water damage resistance and aging resistance, it may not be possible to achieve a good balance while ensuring a certain heating efficiency. In addition, the traditional design method may sacrifice other important performance indicators in the pursuit of a certain performance, resulting in the overall performance of the asphalt mixture being less than ideal.

[0004] For example, the Chinese patent application CN106498825A discloses a method for optimizing the mix ratio design of a heat-conducting SMA modified asphalt mixture for snow-melting roads. The SMA modified asphalt composition includes SBS modified asphalt and stone. The method includes: step 1, determining the gradation of the stone and the optimal oil-stone ratio z of the SBS modified asphalt; step 2, using graphite instead of mineral powder, and performing mix ratio design again, setting the specific amount of graphite instead of mineral powder to x (x = 10% to 30%), the percentage of mineral powder in the mass of the stone to y, taking z + 0.5xy as the median, taking several different oil-stone ratios at intervals of 0.2%, respectively forming Marshall specimens, measuring the volume index, determining the optimal oil-stone ratio of the modified asphalt after adding graphite, and then determining the corresponding gradation, graphite dosage and SBS modified asphalt dosage. The design method of this patent is still to set the dosage gradient first, and then derive the optimal oil-stone ratio. This method does not necessarily achieve the optimal target demand, and it is more troublesome to adjust.

[0005] In summary, the existing asphalt mixture gradation design method has shortcomings in terms of fast electromagnetic response characteristics and comprehensive performance. A new mix design method is needed to solve these problems in order to meet the development needs of modern road engineering. Summary of the invention

[0006] The purpose of the present invention is to provide a method for designing the proportion of fast electromagnetic response asphalt mixture modified by nanofillers. By designing the ratio of nanofillers and asphalt, it is preliminarily determined that the material has a good electromagnetic response effect, and further by determining the nano-binder ratio and the oil-stone ratio, the asphalt mixture gradation is reversed, providing technical support for the asphalt mixture gradation design under specific requirements.

[0007] The purpose of the present invention can be achieved by the following technical solutions:

[0008] A method for designing a ratio of a nanofiller-modified fast electromagnetic response asphalt mixture comprises the following steps:

[0009] S1. Design of the ratio of nanofiller and asphalt: Select different amounts of nanofillers to modify asphalt, add asphalt and stir evenly, then cool and keep warm to obtain a series of asphalt samples, then perform microwave heating, test the temperature of different asphalt samples, and select the asphalt samples with the highest heating rate as candidates for the best nanofiller-to-binder ratio;

[0010] S2. Verification of asphalt mechanical properties: Conduct mechanical property tests and verification on the best candidate for asphalt-binder ratio selected in S1, comprehensively consider the mechanical performance and heating effect, and determine the best asphalt-binder ratio;

[0011] S3, asphalt mixture gradation design: using the best sodium-to-rubber ratio obtained in S2, select several asphalt-to-rock ratios based on experience to prepare asphalt mixture gradation samples, then perform microwave heating on the prepared asphalt mixture gradation samples, test the heating efficiency of different asphalt mixture samples, and select the asphalt-to-rock ratio with heating advantage as an alternative;

[0012] S4. Verification of asphalt mixture performance: Prepare asphalt mixture samples according to the alternative oil-stone ratio designed in S3, and use the Marshall test to verify the performance. Consider the heating efficiency and material properties comprehensively, and select the best oil-stone ratio of the asphalt mixture.

[0013] Furthermore, in S1, the nanofiller is first subjected to high-temperature insulation (the insulation temperature is consistent with the temperature at which the selected asphalt reaches good fluidity, specifically, it can be the mixing temperature of asphalt mixture), and then the asphalt is heated to have good fluidity and then the high-temperature insulation nanofiller is added and stirred so that the nanofiller is fully and evenly dispersed in the asphalt.

[0014] Furthermore, in S1, the number of the best nanostructured carbonyl ratio candidates is two to three.

[0015] Furthermore, in S2, the selection criteria for the optimal nano-binder ratio are: through a pull-out test, the pull-out strength and water damage resistance of asphalt samples with different nano-filler ratios are plotted and compared, and the mechanical properties of the asphalt sample added with the mineral powder asphalt mortar sample with the same nano-filler dosage are used as the standard. Under the condition that the change rate of the pull-out strength before and after immersion in water does not exceed 15%, the nano-binder ratio with the highest heating rate is selected as the optimal nano-binder ratio.

[0016] Furthermore, the pull-out strength change rate formula is calculated as follows:

[0017] Δp=(p 2 -p 1 ) / p 2 ,

[0018] Wherein, Δp is the rate of change of tensile strength;

[0019] p 1 The tensile strength of samples prepared from asphalt mastic with a specific amount of nanofiller;

[0020] p 2 For 1 The tensile strength of samples made from mineral powder asphalt mortar with the same amount of nanofiller.

[0021] Further, in S3, when designing the asphalt-stone ratio, the sum of the nanofiller and the mineral powder is first regarded as the total amount of powder, and then a series of asphalt-stone ratios are selected based on the optimal nano-binder ratio designed in S2 according to the empirically selected asphalt mixture gradation (such as SMA-13 ​​asphalt mixture gradation), and the mineral powder content is calculated. The mixture gradation is the content of aggregates of different particle sizes + powder content + cellulose content + asphalt-stone ratio, wherein the powder content in the present invention is the sum of mineral powder and nanofiller, and the formula is to calculate the mineral powder content.

[0022] Furthermore, in S3, when calculating the asphalt mixture gradation sample under the corresponding asphalt aggregate ratio, the actual content of mineral powder is first calculated by the following formula:

[0023] D = CA × B,

[0024] Where A is the nanofiller-to-bitumen ratio, i.e., the mass ratio of nanofiller to asphalt;

[0025] B is the selected asphalt-to-stone ratio, i.e. the percentage of asphalt in the total mass of aggregate and powder;

[0026] C is the powder content in the asphalt mixture gradation (fixed value, remains unchanged);

[0027] D is the actual content of mineral powder.

[0028] Furthermore, in S3, when selecting based on experience, the specification will have relevant provisions on the range of oil-stone ratio, and the appropriate range of oil-stone ratio can be determined based on the different types of mixtures and the different cellulose selections.

[0029] Furthermore, in S4, the selection criteria for the optimal asphalt-to-stone ratio of asphalt mixture are:

[0030] The performance index of the asphalt mixture sample is verified by the Marshall test. According to the Marshall asphalt-aggregate ratio design method, a curve is drawn to obtain the optimal asphalt-aggregate ratio. The corresponding asphalt-aggregate ratio and the mixture gradation are the optimal asphalt-aggregate ratio and the optimal mixture gradation. The specific process of "drawing a curve to obtain the optimal asphalt-aggregate ratio according to the Marshall asphalt-aggregate ratio design method" here belongs to the conventional technology in this field and will not be repeated here.

[0031] Furthermore, in S4, the performance indicators verified by the Marshall test include relative density, void fraction, stability and flow value.

[0032] The addition of nanofillers will cause certain losses in the performance of the mixture. In order to avoid excessive losses that lead to failure to meet basic performance requirements, the present invention can expand the range of candidate nanofillers to binder ratios during specific operations. If the performance loss is too large, a relatively low nanofiller to binder ratio can be selected for secondary verification until a nanofiller to binder ratio that meets the performance loss limit is found.

[0033] The traditional asphalt mixture gradation design method is limited to one-way logical thinking. It usually assumes several modified material dosages based on literature and experience, then designs the asphalt-stone ratio, and finally tests various aspects of the mixture performance. This method is relatively labor-intensive and it is often difficult to find the most appropriate dosage value.

[0034] The method of first determining the asphalt nanofiller-binder ratio proposed in the present invention can find the dosage value that can improve the electromagnetic response rate of asphalt the most at the beginning of the test, and then use the asphalt-stone ratio and the nanofiller-binder ratio to reversely deduce the actual mineral powder content and gradation design by controlling the total amount of powder to be fixed, so as to obtain the mixture gradation with excellent electromagnetic response rate. Through this asphalt mixture gradation design method, the dosage of nanofillers that can effectively improve the electromagnetic response rate of the material can be determined first, and then the overall gradation of the mixture can be further determined. The design concept reverses the logic of traditional mixture gradation design, can reduce the complicated traditional asphalt mixture modification design process, and more accurately obtain the optimal modified material dosage, opening up the key links of mixture design, and providing technical support for subsequent research. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 It is the parameter curve of Marshall test index;

[0036] Figure 2This is the basic process of the nanofiller modified fast electromagnetic response asphalt mixture ratio design method of the present invention. DETAILED DESCRIPTION

[0037] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.

[0038] In the following examples, the nanofiller A used is a 1:1 mixture of carboxyl iron powder (reduced spherical carbonyl Fe 7439-89-6) and graphite, the asphalt is SBS modified asphalt with a PG grade of 76-22, and the mixture type is SMA-13.

[0039] The rest of the raw materials or processing techniques, unless otherwise specified, are conventional commercially available raw materials or conventional processing techniques in the art.

[0040] Embodiment 1:

[0041] Reference Figure 2 As shown, the present embodiment provides a method for designing a ratio of a nanofiller-modified fast electromagnetic response asphalt mixture, comprising the following steps:

[0042] 1) Design of the ratio of nanofiller and asphalt: The nanofiller A selected in this test was mixed and added at a ratio of 1:1. Four nanofiller-to-binder ratios of 25%, 30%, 35%, and 40% were designed respectively, and a nanofiller-to-binder ratio of 0% was used as a blank control. After preparation, the mixture was placed in a microwave oven and heated for one minute. The surface temperature was recorded with an infrared thermal imager and the heating rate was calculated. The heating rates of asphalt with different nanofiller-to-binder ratios are shown in Table 1. The two to three nanofiller-to-binder ratios with the highest heating rates were found as candidates.

[0043] Table 1 Heating rate of asphalt heated for 60s at different ratios of nano-binder

[0044] Na / Ratio 0 25% 30% 35% 40% Heating rate (℃ / min) 15 22 25 31 45

[0045] 2) Verification of mechanical properties of asphalt: According to the test results in step 1), two asphalt-to-binder ratios of 35% and 40% can be selected, and asphalt mortars with 35% and 40% mineral powder content can be used as control groups, and pull-out tests are carried out accordingly. Four parallel specimens are designed for one group of pull-out tests, and the immersion conditions are 30°C water bath insulation for one day. Before the test, the specimens need to be placed in an environmental box for insulation at 15°C for 2 hours. The test results are shown in Table 2. According to the test results in Table 2, combined with the heating rate in step 1), under the condition that the change rate of pull-out strength before and after immersion does not exceed 15%, the asphalt-to-binder ratio of 35% with the highest heating rate is selected as the optimal asphalt.

[0046] Table 2 Pull-out test results

[0047]

[0048] 3) Asphalt mixture gradation design: Based on experience, the SMA-13 ​​asphalt mixture gradation is selected as shown in the following table. Three asphalt-stone ratios of 5.8%, 6%, and 6.2% are designed respectively. The actual mineral powder content is calculated based on the optimal sodium-binder ratio obtained in step 2). The specific formula is:

[0049] D = CA × B,

[0050] Where A is the nanofiller-to-bitumen ratio, i.e., the mass ratio of nanofiller to asphalt;

[0051] B is the selected asphalt-to-stone ratio, i.e. the percentage of asphalt in the total mass of aggregate and powder;

[0052] C is the powder content in the initial gradation of asphalt mixture;

[0053] D is the actual content of mineral powder.

[0054] Table 3 SMA-13 ​​asphalt mixture gradation

[0055]

[0056] 4) Asphalt mixture performance verification: According to the gradations of three different asphalt-stone ratios calculated in step 3) (the mineral powder* content in Table 4 above is actually the powder content, which is the sum of the actual mineral powder components and nanofillers added. According to the above formula, the actual mineral powder content of different asphalt-stone ratios at a certain nano-binder ratio is calculated, and then the filler part in the table is specifically divided into mineral powder content and nanofiller, and the total filler content remains unchanged), prepare standard Marshall specimens, conduct Marshall stability and flow value tests in accordance with the specifications, record the test results and process the data as shown in Table 4.

[0057] Table 4 Design gradation Marshall test specimen results

[0058]

[0059] According to the test data, Marshall test index parameter curves are drawn respectively, such as Figure 1 As shown in the figure, it can be seen that the oil-stone ratio α corresponding to the maximum relative density of gross volume 1 =6.2%, corresponding to the maximum value of Marshall stability oil-stone ratio α 2 =5.8%, corresponding to the oil-stone ratio of the median porosity α 3 =6.0%, corresponding to the asphalt-rock ratio of the median asphalt saturation 4 =6.0%. For the oil-to-stone ratio range selected for the test, OAC is calculated according to the formula 1 =(α 1 +α2 +α 3 +α 4 ) / 4=6.0%. Determine the oil-stone ratio range in which all indicators meet the requirements of the technical standards for asphalt mixtures, including the oil-stone ratio range in which all indicators meet the requirements of the technical standards for asphalt mixtures, including OAC min =5.7%, OAC max =6.1%, take the average of the two and get OAC 2 =(OAC min +OAC min ) / 2=5.9%. And OAC 1 Between OAC min ~OAC min So take OAC 1 =6.0% is reasonable. 1 and OAC 2 The average value is taken as the optimal oil-stone ratio, that is, OAC = (OAC 1 +OAC 2 ) / 2=5.95%, from which the optimal asphalt-stone ratio can be determined to be 6.0%. At this time, the optimal mixture gradation is shown in the following table.

[0060] Table 5 Optimal gradation design of asphalt mixture

[0061]

[0062] It can be seen that based on the design concept of the present invention, the complicated traditional asphalt mixture modification design process can be effectively shortened, and the optimal modified material dosage obtained is more accurate and closer to the actual optimal situation.

[0063] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.

Claims

1. A method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture, characterized in that: The following steps are involved: S1. Design of the ratio of nanofiller and asphalt: Select different amounts of nanofillers to modify asphalt, add asphalt and stir evenly, then cool and keep warm to obtain a series of asphalt samples, then perform microwave heating, test the temperature of different asphalt samples, and select the asphalt samples with the highest heating rate as candidates for the best nanofiller-to-binder ratio; S2. Verification of asphalt mechanical properties: Conduct mechanical property tests and verification on the best candidate for asphalt-binder ratio selected in S1, comprehensively consider the mechanical performance and heating effect, and determine the best asphalt-binder ratio; S3, asphalt mixture gradation design: using the best sodium-to-rubber ratio obtained in S2, select several asphalt-to-rock ratios based on experience to prepare asphalt mixture gradation samples, then perform microwave heating on the prepared asphalt mixture gradation samples, test the heating efficiency of different asphalt mixture samples, and select the asphalt-to-rock ratio with heating advantage as an alternative; S4. Verification of asphalt mixture performance: Prepare asphalt mixture samples according to the alternative oil-stone ratio designed in S3, and use the Marshall test to verify the performance. Consider the heating efficiency and material properties comprehensively, and select the best oil-stone ratio of the asphalt mixture.

2. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1 is characterized in that: In S1, the nanofiller is firstly heat-insulated at a high temperature, and the heat-insulated temperature is the mixing temperature of the asphalt mixture. Then, after the asphalt is heated to have good fluidity, the high-temperature heat-insulated nanofiller is added and stirred so that the nanofiller is fully and evenly dispersed in the asphalt.

3. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1, characterized in that: In S1, the number of candidates for the best sodium-to-rubber ratio is two to three.

4. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1, characterized in that: In S2, the selection criteria for the best nano-binder ratio are: by comparing the tensile strength and water damage resistance of asphalt samples with different nano-binder ratios through pull-out tests, taking the mechanical properties of mineral powder asphalt mortar samples with the same nano-filler content as the standard, and under the condition that the change rate of tensile strength before and after immersion in water does not exceed 15%, the nano-binder ratio with the highest heating rate is selected as the best nano-binder ratio.

5. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 4 is characterized in that: In S2, the calculation formula of the pull-out strength change rate is as follows: Δp=(p2-p1) / p2, Wherein, Δp is the rate of change of tensile strength; p1 is the pull-out strength of the sample made from asphalt mortar with a specific amount of nanofiller; p2 is the tensile strength of the sample made from mineral powder asphalt mortar with the same nanofiller dosage as in p1.

6. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1, characterized in that: In S3, when designing the asphalt-stone ratio, the sum of the nanofiller and the mineral powder is first regarded as the total amount of powder. Then, based on the optimal nanofiller-binder ratio designed in S2 and the asphalt mixture grading selected according to experience, a series of asphalt-stone ratios are selected, and the mineral powder content is calculated and determined.

7. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 6, characterized in that: In S3, when calculating the asphalt mixture gradation of the asphalt mixture gradation sample at the corresponding asphalt aggregate ratio, the actual content of mineral powder is calculated by the following formula: D = CA × B, Where A is the nanofiller-to-bitumen ratio, i.e., the mass ratio of nanofiller to asphalt; B is the selected asphalt-to-stone ratio, i.e. the percentage of asphalt in the total mass of aggregate and powder; C is the powder content in the asphalt mixture gradation; D is the actual content of mineral powder.

8. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1, characterized in that: In S4, the selection criteria for the best asphalt-to-stone ratio of asphalt mixture are: The performance indicators of asphalt mixture samples are verified by Marshall test. According to the Marshall asphalt-aggregate ratio design method, a curve is drawn to obtain the optimal asphalt-aggregate ratio. The corresponding asphalt-aggregate ratio and mixture gradation are the optimal asphalt-aggregate ratio and the optimal mixture gradation.

9. The method for designing the proportion of a nanofiller-modified fast electromagnetic response asphalt mixture according to claim 1 or 8, characterized in that: In S4, the performance indicators verified by the Marshall test include relative density, void ratio, stability and flow value.

Citation Information

Patent Citations

  • Mix proportion design and optimization method of thermal-conduction SMA modified asphalt mixture applied to snow-melting roads

    CN106498825A